Blood Pressure Variability and Optimal Cerebral Perfusion Pressure—New Therapeutic Targets in Traumatic Brain Injury. Issue 3 (6th December 2019) - Svedung Wettervik, Teodor; Howells, Timothy; Lewén, Anders; Enblad, Per
Abstract: BACKGROUND: Optimal cerebral perfusion pressure (CPPopt) is an autoregulatory-oriented target in the neurointensive care (NIC) of patients with traumatic brain injury (TBI), and deviation from CPPopt is associated with poor outcome. We recently found that blood pressure variability (BPV) is associated with deviation from CPPopt. OBJECTIVE: To evaluate BPV and other variables related to deviation from CPPopt and to evaluate challenges and strategies for autoregulatory-oriented treatment in TBI. METHODS: Data including arterial blood pressure and intracranial pressure (ICP) from 362 TBI patients treated at the NIC unit, Uppsala University Hospital, Sweden, between 2008 and 2016, were retrospectively analyzed day 2 to 5. RESULTS: Higher BPV was a strong predictor of both CPP deviation below and above CPPopt after multiple regression analyses. There was no other explanatory variable for CPP deviation above CPPopt, whereas also higher ICP and worse autoregulation (higher pressure reactivity index) were associated with CPP deviation below CPPopt. A higher BPV was, in turn, explained by older age, lower ICP, higher mean arterial blood pressure, and higher slow arterial blood pressure amplitude (0.018-0.067 Hz). CONCLUSION: BPV was strongly associated with deviation from CPPopt. High age is a risk factor for high BPV and hence CPP insults. Our treatment protocol is focused on avoiding CPP below 60 mm Hg. It is possible that a more restrictive upper level could generate more stable blood pressure and less deviation from CPPopt.